Hambatan Hukum untuk Penikmatan Hak atas Pekerjaan bagi Pekerja dengan Disabilitas - Ayunita Nur Rohanawati; Sahid Hadi; Taufiq Rahman (Jurnal HAM, 2023)
This article focuses on the enjoyment of the right to work for workers with disabilities. This focus is driven by the fact that there are still many discriminatory practices for workers with disabilities in the workplace. This study identifies, for instance, a worker with sensory and physical disabilities that is assigned to a not accessible field of work. This assignment presents barriers faced by the worker and results in the termination of the worker's employment. Based on this fact, this article addresses two research questions. What is the legal barrier to the enjoyment of the right to work for workers with disabilities? What adequate interventions should the state take to ensure equality and non-discrimination for workers with disabilities? This normative study answers these two questions by analyzing the norms of Law No. 13/2003 on Manpower with the component of legal barrier in the social model for disability. This study proves that the provision in the Manpower Law is categorized as a legal barrier to the enjoyment of the right to work for workers with disabilities. Therefore, this study encourages the state's legislative function to complement the provisions of the Law with a substance that requires every employers to ensure that their business governance is inclusive and accessible to the diversity of workers with disabilities based on equal rights.